1995
DOI: 10.1016/0167-4889(95)00138-8
|View full text |Cite
|
Sign up to set email alerts
|

BAP2, a gene encoding a permease for branched-chain amino acids in Saccharomyces cerevisiae

Abstract: To select the gene coding for an isoleucine permease, an isoleucine dependent strain (ilv1 cha1) was transformed with a yeast genomic multicopy library, and colonies growing at a low isoleucine concentration were selected. Partial sequencing of the responsible plasmid insert revealed the presence of a previously sequenced 609 codon open reading frame of chromosome II with homology to known permeases. Deletion, extra dosage and C-terminal truncation of this gene were constructed in a strain lacking the general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
0
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(120 citation statements)
references
References 30 publications
4
113
0
3
Order By: Relevance
“…We wondered whether the inability of an ero1-1 leu2 strain to grow on 30 mg/l leucine can be explained by a dysfunction of Bap2p. Previous studies indicate that the lack of the C-terminal 29 residues of Bap2p causes increased capacity for uptake of isoleucine, leucine, and valine, 17) due to increased stability of the permease. 20) Hence we transformed the ero1-1 leu2 strain with a plasmid carrying the truncated allele (BAP2Á29), and observed that this caused a moderate gain in the ability to grow on SC medium at 30 C (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We wondered whether the inability of an ero1-1 leu2 strain to grow on 30 mg/l leucine can be explained by a dysfunction of Bap2p. Previous studies indicate that the lack of the C-terminal 29 residues of Bap2p causes increased capacity for uptake of isoleucine, leucine, and valine, 17) due to increased stability of the permease. 20) Hence we transformed the ero1-1 leu2 strain with a plasmid carrying the truncated allele (BAP2Á29), and observed that this caused a moderate gain in the ability to grow on SC medium at 30 C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bap2p has decreased stability in an ero1-1 strain On preferred nitrogen sources, the main leucine import system in yeast is the Bap2 protein, 17,30) an integral protein in the plasma membrane (PM). We wondered whether the inability of an ero1-1 leu2 strain to grow on 30 mg/l leucine can be explained by a dysfunction of Bap2p.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After incubating this mixture at 37 uC, amino acid uptake was stopped by addition of 5 ml ice-cold PBS. The cells were collected on a Whatman GF/C glass microfibre filter, washed three times with cold PBS, air-dried and their radioactivity measured in a scintillation counter (Grauslund et al, 1995). All uptake studies were done in triplicate, and mean values were determined.…”
Section: Methodsmentioning
confidence: 99%
“…Many of these have been identified previously through mutant studies and their substrate specificity is known; others are open reading frames, identified in the Yeast Genome Project as homologous to other members of the family (Nelissen et al, 1995). The known amino acid permeases show several common features: a length of approximately 600 amino acids, a central hydrophobic section which contains 12 putative membrane-spanning domains, no N-terminal signal sequence and a C-terminal which is fairly hydrophilic and may be involved in permease regulation (Grausland et al, 1995;Zhu et al, 1996).…”
Section: Introductionmentioning
confidence: 99%